2013
DOI: 10.1007/s00216-013-7268-4
|View full text |Cite
|
Sign up to set email alerts
|

Multiclass method for antimicrobial analysis in animal feeds by liquid chromatography–tandem mass spectrometry

Abstract: A rapid multiclass method that covers 50 antimicrobials from 13 different families in animal feeds was developed. Samples were extracted using a mixture of methanol, acetonitrile and a McIlvaine buffer combined with sonication. Feed extracts were simply diluted prior to injection, since the clean-up strategies that were tested, based on either solid-phase extraction or dispersive solid-phase extraction, were ineffective at minimizing matrix-related signal suppression/enhancement. Analysis was carried out by li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 8 publications
1
14
0
Order By: Relevance
“…Although many authors have used ACN or a mixture of ACN, methanol, and water (Cronly et al, 2010;Lopes et al, 2012;Wang et al, 2014) to precipitate proteins and eliminate other interferences, we got best results with methanol. In agreement with other studies (Borr as et al, 2013;Lopes et al, 2012), we found ACN to yield "cleaner" extracts, but methanol to have a much better extraction capacity: some compounds present after methanol extraction were undetectable after ACN extraction. It is worth noting that Borr as, Company o, & Guiteras (2011) obtained "dirtier" extracts when ACN was used.…”
Section: Resultssupporting
confidence: 93%
“…Although many authors have used ACN or a mixture of ACN, methanol, and water (Cronly et al, 2010;Lopes et al, 2012;Wang et al, 2014) to precipitate proteins and eliminate other interferences, we got best results with methanol. In agreement with other studies (Borr as et al, 2013;Lopes et al, 2012), we found ACN to yield "cleaner" extracts, but methanol to have a much better extraction capacity: some compounds present after methanol extraction were undetectable after ACN extraction. It is worth noting that Borr as, Company o, & Guiteras (2011) obtained "dirtier" extracts when ACN was used.…”
Section: Resultssupporting
confidence: 93%
“…Feed samples, collected from farms and feed mills, that were received by the Laboratori Agroalimentari of the Generalitat de Catalunya (LAC) for their analysis by UHPLC-MS/MS [10] were used to demonstrate the applicability of the DESI-HRMS in this study.…”
Section: Samples and Sample Preparationmentioning
confidence: 99%
“…The criteria applied to confirm the presence of the suspected compounds were the following: a mass accuracy of less than 5 ppm on the exact mass, a minimum signal-to-noise ratio of 3:1, and an isotope cluster fit higher than 80 % (both mass relative deviation and relative intensity differences, for each isotope peak within the cluster ion, were taken into account). Feed samples were also analyzed by a well-established UHPLC-MS/MS method for the quantification of the identified compounds [10]. Table 1 lists the positive samples and the veterinary drugs identified along with the DESI-HRMS identification criteria and the quantitative results obtained by target UHPLC-MS/ MS method.…”
Section: Desi-hrms Screening Of Feed Samplesmentioning
confidence: 99%
See 2 more Smart Citations